Pelatihan Pelatihan Pembuatan Kursi Lesehan Hias dari Kaleng Plastik Bekas pada Karang Taruna New Brigade Taruma Negara Banyuanyar - Rifai, Dian; Kristiana Seftianingsih, Dina; Syahnas Paradita, Dea; Tri Hastiuti , Henny (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This dedication is motivated by the abundance of used plastic waste packaging for jam bread in the RW IX area of Banyuanyar Village which has accumulated and is not utilized so that it becomes a problem for the local residents. The increase in plastic waste used for bread jam is due to the fact that bread jam is also used as an ingredient for toast that is sold. This ceremony aims to, in addition to reducing the accumulation of used solid waste packaging for jam bread, to increase the economic value of becoming cross-legged chairs that have artistic value and have a selling value. This service activity also intends to instill a creative spirit in the youth of RW IX, Banyuanyar Village in creating used plastic jam packaging by arranging used plastic cans in such a way as to form a cross-legged chair which is then decorated using knick-knacks that can cover the cans and become a chair that has artistic and economic value